World Control of Atomic Energy. - Langmuir, Irving (Transactions of the American Philosophical Society, 2024)
The article "World Control of Atomic Energy" by Irving Langmuir discusses the necessity for effective world control of atomic energy, highlighting the proposed solutions and potential challenges. Langmuir emphasizes the importance of consolidating and extending the authority of the United Nations Organization to establish a rule of law among nations. The article also explores the potential consequences of an atomic armament race, particularly focusing on the capabilities and motivations of different nations, such as Russia and the United States. Langmuir concludes by advocating for mutual tolerance and understanding between nations to achieve effective world government and prevent the scourge of war.